Analysis of Methods for Controlling Ball Drum Mills at Hard Materials Grinding - Lymych, Vasyl; Fedoryshyn, Roman (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The technological process of grinding hard materials with application of ball drum mills has been analyzed. The advantages and disadvantages of ball drum mills application for grinding hard materials have been determined. The analysis of methods for ball drum mills control has been conducted based on the vibration acceleration signal from the mill’s input support, the differential pressure across the mill drum, the temperature of the air mixture at the mill’s outlet and the active power signal of the mill drive. Проаналізовано технологічний процес подрібнення твердих матеріалів із застосуванням кульових барабанних млинів. Визначено переваги та недоліки застосування кульових барабанних млинів для подрібнення твердих матеріалів. Проведено аналіз методів керування кульовими барабанними млинами на основі сигналу віброприскорення з вхідної опори млина, перепаду тиску на барабані млина, температури повітряної суміші на виході з млина та сигналу активної потужності приводу млина.